2012
DOI: 10.1021/cg300977e
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origins of Conformational Disorder in the Crystalline Polymorphs of Irbesartan

Abstract: The characterization of crystalline polymorphs of drug molecules is an area of great interest since these variations in solid-state structure directly influence the physical properties of such substances. Terahertz spectroscopy provides a powerful analytical tool for these investigations and has been used here to study tautomeric polymorphism and conformational disorder in crystallized irbesartan, an antihypertensive medication. The low-frequency (<90 cm −1 ) terahertz spectra of both irbesartan Form A and For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…Terahertz spectra revealed not only distinct features for each polymorph but also allowed for characterisation of the conformational disorder. The subsequent computational simulations of the vibrational modes in periodic structures showed that the disorder in this crystal structure arises from a competition between internal conformational strain and external cohesive binding [51].…”
Section: Partly Disordered Systemsmentioning
confidence: 95%
See 1 more Smart Citation
“…Terahertz spectra revealed not only distinct features for each polymorph but also allowed for characterisation of the conformational disorder. The subsequent computational simulations of the vibrational modes in periodic structures showed that the disorder in this crystal structure arises from a competition between internal conformational strain and external cohesive binding [51].…”
Section: Partly Disordered Systemsmentioning
confidence: 95%
“…Apart from the identification of crystalline polymorphs, terahertz spectroscopy is an effective tool to probe subtle disorder within the solid-state structure. An example system is the tautomeric polymorphism of irbesartan [51]. Irbesartan is known to exist in at least two different polymorphs, forms A and B. Irbesartan form B exhibits conformational disorder within the n-butyl hydrocarbon chain.…”
Section: Partly Disordered Systemsmentioning
confidence: 99%
“…Further examples that both demonstrate the high sensitivity of THz-TDS for supermolecular structure and explain this sensitivity at the molecular level by means of computational techniques (as discussed in more detail in the next section) are the recent studies by Delaney and coworkers on the conformational disorder in irbesartan 165 and on the interplay between conformational strain and cohesion binding that was found to play a key role in the stability of gabapentin polymorphs 166 as well as aripiprazole, 167 and by Pellizzeri et al on how THz-TDS can play an important role as a complementary technique to X-ray diffraction in the characterization of new polymorphs. 168 Succinonitrile forms a plastic crystal that is flexible and exhibits strong disorder in its crystalline phase at room temperature but that can be ''frozen out'' at lower temperature, leading to a much more ordered, rigid-crystal phase that exhibits distinct, albeit broad, spectra features at terahertz frequencies.…”
Section: Crystalline Systemsmentioning
confidence: 98%
“…25 However, the complexity of the low-frequency vibrational motions means that advanced computational methods are required in order to interpret and assign the experimental spectra, which are often computationally expensive due to the rigorous criteria necessary to accurately represent the weak forces found in molecular crystals. [26][27][28] It is not surprising then that while the low-frequency spectra of the indomethacin polymorphs have been previously reported, 29,30 no spectral assignment has been performed to date.…”
Section: Introductionmentioning
confidence: 99%